Mesozooplankton assemblages in two bays in the Beagle Channel (Argentina) during January, 2001 - Fernandez Severini, Melisa Daiana; Hoffmeyer, Monica Susana
This paper describes the composition and abundance of mesozooplankton of Bahía Ushuaia and Bahía Golondrina. These small bays are located in the northern Beagle Channel. Sampling was carried out during January 20 - 23, 2001 and samples were collected from the upper layer at nine stations. This study is the first research on mesozooplankton specifically in this part of the Beagle Channel. Due to their dominance in the mesozooplankton community, we compared our Copepoda data with those reported by other authors from Antarctic coastal environments. By applying cluster analysis we found two station groups in both bays: one in slightly polluted zones and the other in undisturbed external zones. Four assemblages in Bahía Ushuaia and two in Bahía Golondrina were determined by using non-metric multidimensional scaling (MDS) and cluster analysis. Mesozooplanktonic assemblages presented a certain resemblance in zones with and without anthropogenic influence. Most of the copepod species in our samples are typical of the Subantarctic region. Oithona similis (=0. helgolandica sensu Ramírez, 1966), Oncaea curvata and Ctelocalanus citer show either similar or higher abundances at Antarctic coastal sites, including the upper layer in oceanic areas, than in Subantarctic coastal localities. This means that, in agreement with other findings, the Polar Front is not likely a major geographic boundary for the distribution of those species. Fil: Fernandez Severini, Melisa Daiana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina Fil: Hoffmeyer, Monica Susana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina